Systematic Review: Phytochemical Content and Pharmacological Effects of Chrysanthemum sp. - Mutiah, Roihatul; Marsyah, Alpionita; Saputra, Azian Firman (Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR); Vol 1 (2021): Proceedings of International Pharmacy Ulul Albab Conference and Seminar (PLANAR)DO - 10.18860/planar.v1i0.1457, 2021)
Chrysanthemum sp.  is a plant often used by the community as an ornamental plant, drink, and traditional medicine. This study aims to examine the plant Chrysanthemum sp.  from the aspect of phytochemical and pharmacological activity. The review method used in this study is the PRISMA method. Sources of data obtained using databases electronic from PubMed and Google Scholar. This review shows that plants  Chrysanthemum sp. have phytochemical and pharmacological potential. The compounds contained in theplant Chrysanthemum sp. are morphine, genistein, hydantoin, limonene, g-terpinene, a-pinene, a-terpenyl acetate, 4-terpenyl acetate, a-calacorene, a-cedrene, b-bourbobene, elemol, 2- hexenal, and orphenadrine. Chrysanthemum   sp. plants have anticancer, antibacterial, antioxidant, antifungal, analgesic, anti-inflammatory, and anticonsulvan activities.